Casos reais de implantaç\~ao do modelo de gest\~ao do conhecimento para a administraç\~ao pública brasileira: A experiência do Governo de Minas Gerais - Fábio Ferreira Batista; Margarida Maria Souto Fantoni; Marco Aurélio Zancanela do Carmo; Renato de Alcino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper analyses the application of the knowledge management framework for the Brazilian public administration (MGCAPB) and the methodology of Knowledge Management Plan implementation (PGC), both based on the book published by Ipea entitled Knowledge Management Framework for the Brazilian Public Administration (Batista, 2012). The work presents the MGCAPB and the implementation stages of the PGC, the KM history in the government of Minas Gerais and the debate about the foundations of the framework and KM processes organization. Moreover, it describes KM implementation based on the state plan and sectorial plans; the MGCAPB implementation process in the Civil Police of Minas Gerais (PCMG), the MGCAPB implementation in the Military Police of Minas Gerais (PMMG). Finally, the paper points out lessons learned with the application of the MGCAPB and the methodology of KM Plan implementation, as well as preliminary results achieved by three agencies of the Minas Gerais government. The authors argue that the experience of Minas Gerais government shows that both the framework and the methodology of KM Plan implementation (PGC) may be useful for other state governments. The paper stresses also that the experience of the Planning and Management Secretariat of Minas Gerais (Seplag/MG), PCMG and PMMG and the beginning of the implementation of KM sectorial plans and of the KM state plan are very recent so it is early to assess the KM initiatives impact on organizational performance. Therefore, future studies are recommended to verify if KM initiatives are bringing organizational results such as: process efficiency, quality improvement of services provided for citizens and projects and programs effectiveness.
Keywords: H80; 330; knowledge management in the public administration; state government